1548. Risk of Severe Herpes Zoster (HZ) in Allogeneic Hematopoietic-Cell Transplantation (HCT) Recipients. (26th November 2018) - Baumrin, Emily; Cheng, Matthew P; Kanjilal, Sanjat; Issa, Nicolas; Baden, Lindsey
Abstract: Background: Allogeneic-HCT recipients are at increased risk for varicella zoster virus (VZV) reactivation and associated complications. Prevalence, timing, and risk factors for severe HZ are uncertain in the era of acyclovir (ACV) prophylaxis. Identification of patients at risk for severe HZ can help target need for prolonged prophylaxis or vaccine administration. In this study, we characterized HZ infection requiring hospitalization in a cohort of allogeneic HCT recipients. Methods: We performed a retrospective, single-center, cohort study of all patients who underwent allogeneic HCT transplantation from October 2006–December 2015. We defined severe HZ as infection requiring hospitalization or administration of IV antiviral medication. We defined HZ diagnosis by either microbiology confirmatory testing or classic dermatomal examination as agreed upon by two or more clinicians. We followed patients until December 2017 for the development of HZ complications. Results: In a cohort of 2, 163 allogeneic HCT recipients, 23 patients (1.1%) developed severe HZ infection, 14 had microbiological confirmation and nine diagnosed clinically. The median age was 37 years (range 18–63); 13/23 (56.5%) were male. Six patients had dermatomal HZ, five with disseminated cutaneous HZ, five with HZ ophthalmicus (one with retinal necrosis), three with VZV meningitis/encephalitis, two with VZV pneumonia, one with VZV viremia, and one with erythema multiforme with mucosal involvement. Ninety-day mortality from onset of diagnosis was 5/23 (21.7%). HZ reactivation occured a median of 14 months after transplant (range 4-day pre-HCT to 80 months). Twelve patients (52.2%) were compliant on ACV prophylaxis at the time of reactivation, of which 10 (83.3%) were on concurrent immunosuppression, including five (41.6%) on a steroid dose >20 mg prednisone per day. In contrast, only 4/11 (36.4%) patients off ACV prophylaxis were on immunosuppression. Conclusion: In the era of ACV prophylaxis, severe HZ reactivation was identified in 1.1% of HCT recipients. The majority of cases occurred < 24 months after transplant despite ACV use in many. HZ virus vaccination might be an additional means of prophylaxis in this vulnerable group. Disclosures: All authors: No reported disclosures.